Fooling System 1 in the field of perception: Failure to intuitively detect attribute substitution in the flushtration count illusion. Issue 11 (November 2022) - Thomas, Cyril; Botella, Marion; Didierjean, André
To facilitate our interactions with the surroundings, the human brain sometimes reshapes the situations that it faces to simplify them. This phenomenon has been widely studied in the context of reasoning, especially through the attribute substitution error. It has however been given much less attention in the field of perception. Recent research on the bat-and-ball problem suggests that reasoners are able to intuitively detect attribute substitution errors. Using a perceptual illusion drawn from the field of magic, we investigate the extent to which a perceptual form of attribute substitution depends on executive resources and can be detected. We also investigate the relationship between susceptibility to attribute substitution error in the flushtration count illusion and in a French adaptation of the bat-and-ball problem. Finally, we investigate the link between the intuitive cognitive style (assessed by the cognitive reflection test) and the susceptibility to the flushtration count illusion. Our results suggest that participants do not detect perceptual attribute substitution error, that this phenomenon could be independent of the executive resources allocated to the task, and could rest on mechanisms distinct from those that produce errors in reasoning. We discuss differences between these two phenomena, and factors that may explain them.